Features of self-tolerance loss in patients with different clinical phenotypes of myasthenia - Klimova, E. M.; Minuchin, D. V.; Drozdova, L. A.; Lavinskaya, E. V.; Kordon, T. I.; Kalashnykova, Y. V. (Regulatory Mechanisms in Biosystems, 2018)
The incidence of myasthenia gravis which is characterized by progressive muscular weakness on the background of structural disorders of the thymus, has increased. Myasthenia gravis is a multifactorial autoimmune disease, it has a pronounced clinical heterogeneity, and therefore the standard diagnostic and treatment protocol is not always effective. To substantiate an individual approach to the treatment of various clinical forms of myasthenia, we conducted a study of mechanisms and markers of loss of central and peripheral self-tolerance in thymus-independent myasthenia (M) and thymus-dependent myasthenia gravis with thymus hyperplasia (MH) and thymoma (MT), involving a total of 427 patients examined. In patients with different phenotypes of myasthenia, we used the methods of spectrophotometry, flow cytometry, enzyme immunoassay. In patients with MH on the background of lymphofollicular thymus hyperplasia we revealed a pronounced humoral sensitization in comparison with the reference values: the concentration of C4 complement, C-reactive protein, circulating immune complexes and the initiation of an indirect autoimmune reaction a reliable increase in autoantibodies (AAbs) to the α1 and α7 subunit of subunit of nicotinic receptors (nAChR). In M and MT groups a high similar titer of AAbs to other epitopes was revealed: DNA, β2-glycoprotein I, membranes of intestinal and stomach cells, lung, liver, kidney cells. A pronounced blast-transforming response to the presence of the mitogen PHA was revealed in the MT group. In the MT group, a decrease in the content of CD4+ CD28+ co-stimulatory molecules and in the MH group, a decrease in СD4+ CD25+ Treg lymphocytes was revealed. Individual methods for correcting the loss of self-tolerance in patients with different clinical phenotypes of myasthenia were justified taking into account the use of immunosuppression, specific viral-neutralizing immunoglobulins and massive IgG immunoglobulin therapy, and the application of anti-inflammatory recombinant interleukins.